Razvoj sposobnosti zaznavanja komičnega - Kordigel Aberšek, Metka (Otrok in knjiga, 1997)
Comic in literature is not something factual, tangible and provable like a chapter, acts, onomatopoeia, metaphors, but it constitutes when a literary text comes in touch with a reader in the process of reception - or not, if reader's horizon of expectation does not accept an offered opportunity for laughter. Hence it is reasonable to think if we are able to (within the science of a young reader, especially observing a child's receptive development) notice also the changes within the question what a child of a certain age perceives as comic. The perception of comic is, either of a child or an adult, linked with the so called incogruence or inconsistency with any of the mind maps, where our knowledge and cognition of the world and its rules, are stored. Any alienation from the former experience and logic certainly cannot be comic. Most of incongruent stimulations in our lives release serious processes: learning. In order to perceive extraordinary as comic there are three conditions to be fulfilled: Your child has to have at least an approximate structured vision how comic would act in case if it were not comic / a child needs a realised relevant (linguistic, social, logic ...) mind map. To some extent he/she has to be able to decide upon extraordinary, comic: shall he/she modify it with a process of fantasy assimilation or a realistic assimilation / accommodation. It means that children ought to know or at least have a premonition where the border between reality and imagination is. Finally, a child has to be able to perceive a comic mind frame, since the incogruence appears to be comic only when accompanied by the so called set. The study of comic shows that children face such problems quite often. The more careful studying of developing the mentioned components,necessary for the perception of comic, shows that this ability (like other segments of receptive ability) is closely linked with a child's personal growth. That means that the ability to perceive comic develops in such a way that a child passes from one typical phase of the progress to another. The continuation of developing phases cannot be altered and particular phases not be overcome. A duration of a phase is individual, the bridges among the phases are erased. In other words: in the beginning of one phase the characteristics of the previous phase can still be heard and towardsthe end of one phase of development there are elements appearing, typical for the following phase
Keywords: mladinska književnost; young adult literature; komično; zaznavanje; literarna recepcija; otroci; child; bralci; bralni razvoj